Analysis of buckling stability behavior of hybrid plate using Ritz approach and numerical simulation. (December 2021) - Aguib, S.; Chikh, N.; Kobzili, L.; Djedid, T.; Nour, A.; Meloussi, M.
Abstract: In this article, we studied the instability phenomenon of plate buckling made of steel (E36-S355), and magnetorheological elastomer subject to compression loading. The study of the magnetic field intensity influence on the buckling instability of compressed hybrid plates is done by a mathematical development using the Ritz approach and by a numerical simulation under the Abaqus software. The obtained results show clearly that we can control the instabilities of the adaptive smart plate's behavior by the magnetic field, and the orientation angle of pseudo-fibers formed by the iron particles; depending on the variation of the angle direction of the magnetic field.